Perhutanan Sosial di Sumatra Barat: Tinjauan Regulasi dan Implementasinya pada Hutan Nagari Salibutan - Nurwansyah; Hariadi Kartodihardjo; Iin Ichwandi (Faculty of Forestry Universitas Gadjah Mada, 2024)
Social forestry is a program designed to address tenure conflicts, improve community welfare, and enhance environmental quality. Achieving the objectives of social forestry is not only limited to obtaining permits but needs more advanced, concrete, innovative business development that anticipates future challenges and prospects. Therefore, this research aimed to analyze West Sumatra Governor Regulation No. 52/2018 on the Implementation of Social Forestry Facilitation and its practical application in Hutan Nagari Salibutan. Data collection in this research included in-depth interviews and a literature review, while data analysis used descriptive qualitative methods, content analysis, and policy implementation. The results showed that Governor Regulation of West Sumatra No. 52/2018 supported national policy by accelerating social forestry, resolving tenure conflicts, and synchronizing the roles of various stakeholders. This Governor Regulation served as the technical reference in the field, and it comprised facilitation, institutionalization, monitoring and evaluation, and financing. Additionally, the implementation of regulations in Salibutan Nagari Forest correlated with these provisions, as evidenced by the activities carried out by the Forestry Service and the social forestry acceleration working group in collaboration with the Nagari Salibutan forest management institution. The consistency between the regulation's content and field implementation reflected this correlation.